Antibody Fc-chimerism and effector functions: When IgG takes advantage of IgA - Cottignies-Calamarte, Andréa; Tudor, Daniela; Bomsel, Morgane (Frontiers in Immunology, 2023)
Recent advances in the development of therapeutic antibodies (Abs) have greatly improved the treatment of otherwise drug-resistant cancers and autoimmune diseases. Antibody activities are mediated by both their Fab and the Fc. However, therapeutic Abs base their protective mechanisms on Fc-mediated effector functions resulting in the activation of innate immune cells by FcRs. Therefore, Fc-bioengineering has been widely used to maximise the efficacy and convenience of therapeutic antibodies. Today, IgG remains the only commercially available therapeutic Abs, at the expense of other isotypes. Indeed, production, sampling, analysis and related in vivo studies are easier to perform with IgG than with IgA due to well-developed tools. However, attention to IgA is growing, despite a shorter serum half-life and a more difficult sampling and purification than IgG. In particular, the paradigm that the effector functions of IgG surpass those of IgA has been experimentally challenged. IgA has been shown to bind to its Fc receptor (FcR) on effector cells of innate immunity with greater efficiency than IgG, resulting in more potent IgA-mediated effector functions in vitro and better survival of treated animals. In addition, the two isotypes have been shown to act synergistically. As a result, new therapeutic formats of Abs are currently emerging, in particular that of chimeric Abs containing two tandemly expressed Fc, one from IgG (Fcγ) and one from IgA (Fcα). By binding both FcγR and FcαR on effector cells, these new chimeras showed improved effector functions in vitro that could be translated in vivo. Furthermore, these chimeras retain an IgG-like half-life in the blood, which could improve Ab-based therapies, including in AIDS. This review provides the rationale, based on the biology of IgA and IgG, for the development of Fcγ and Fcα chimeras as therapeutic Abs, offering promising opportunities for HIV-1 infected patients. We will first describe the main features of the IgA- and IgG-specific Fc-mediated signalling pathways and their respective functional differences. We will then summarise the very promising results on Fcγ and Fcα containing chimeras in cancer treatment. Finally, we will discuss the impact of Fcα-Fcγ chimerism in prevention/treatment strategies against infectious diseases such as HIV-1.